ANÁLISE MICROBIOLÓGICA DA ÁGUA NO MUNICÍPIO DE SÃO MIGUEL DOS CAMPOS, ALAGOAS - Albuquerque, Maria Vitoria Rocha de; Albernaz, Giovanna Garcia; Costa, Isabelle do Nascimento; Figueirêdo, Bárbara Camboim Lopes de; Almeida, Sheilla Karynna Macedo de (Gep News, 2019)
Trabalho premiado em TERCEIRO LUGAR - Modalidade Comunicação Oral